Development of an International Tool for Students to Record and Reflect on Patient Safety Learning Experiences. Issue 3 (6th May 2022) - Steven, Alison; Pearson, Pauline; Turunen, Hannele; Myhre, Kristin; Sasso, Loredana; Vizcaya-Moreno, Maria Flores; Pérez-Cañaveras, Rosa María; Sara-Aho, Arja; Bagnasco, Annamaria; Aleo, Giuseppe; Patterson, Lucy; Larkin, Valerie; et al.
Abstract : Background: Underpinning all nursing education is the development of safe practitioners who provide quality care. Learning in practice settings is important, but student experiences vary. Purpose: This study aimed to systematically develop a robust multilingual, multiprofessional data collection tool, which prompts students to describe and reflect on patient safety experiences. Approach: Core to a 3-year, 5-country, European project was development of the SLIPPS (Sharing Learning from Practice for Patient Safety) Learning Event Recording Tool (SLERT). Tool construction drew on literature, theory, multinational and multidisciplinary experience, and involved pretesting and translation. Piloting included assessing usability and an initial exploration of impact via student interviews. Outcomes: The final SLERT (provided for readers) is freely available in 5 languages and has face validity for nursing across 5 countries. Student reports (n = 368) were collected using the tool. Conclusions: The tool functions well in assisting student learning and for collecting data. Interviews indicated the tool promoted individual learning and has potential for wider clinical teams.